2016
DOI: 10.4136/ambi-agua.1830
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of methylmercury in fish tissue from the Roosevelt River, Southwestern Amazon basin

Abstract: Mercury is a major pollutant in the Amazon River system, and its levels in fish and human hair are usually above the limit recommended by health agencies. The objective of this study was to analyze the methylmercury (MeHg) concentration in fish tissue from the Roosevelt River. The river’s water velocity, depth, pH, temperature, electrical conductivity, dissolved oxygen and substrate type were measured, and fifty specimens distributed in 14 fish species were collected. A total of 64.3% of the sampled species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
1
2
0
2
Order By: Relevance
“…Mercury concentrations in fish from Tapajós basin (in which Teles Pires River is part of) vary between studies, most likely as a result of collection site relating to anthropogenic activities, including gold-digging, deforestation, and agriculture ( Table 6). For B. cuvieri, on Teles Pires River in a preserved area (Castilhos et al, 2012), and on Rio Roosevelt belonging to Madeira River basin (Dos Anjos et al, 2016) in an area with deforestation and golddigging, studies showed higher concentrations of mercury compared to data from present study ( Table 6). There are studies showing higher mercury concentrations than present study for H. armatus with its counterpart Hydrolycus scomberoides in Tocantis River in an area with gold-digging and deforestation (Milhomem-Filho et al, 2016), in Tapajós River in an area with golddigging, deforestation and agriculture (Bidone et al, 1997), on Teles Pires River in an area with gold-digging and deforestation (Uryu et al, 2001).…”
Section: Total Mercury In Fish From Tele Pires Riversupporting
confidence: 42%
“…Mercury concentrations in fish from Tapajós basin (in which Teles Pires River is part of) vary between studies, most likely as a result of collection site relating to anthropogenic activities, including gold-digging, deforestation, and agriculture ( Table 6). For B. cuvieri, on Teles Pires River in a preserved area (Castilhos et al, 2012), and on Rio Roosevelt belonging to Madeira River basin (Dos Anjos et al, 2016) in an area with deforestation and golddigging, studies showed higher concentrations of mercury compared to data from present study ( Table 6). There are studies showing higher mercury concentrations than present study for H. armatus with its counterpart Hydrolycus scomberoides in Tocantis River in an area with gold-digging and deforestation (Milhomem-Filho et al, 2016), in Tapajós River in an area with golddigging, deforestation and agriculture (Bidone et al, 1997), on Teles Pires River in an area with gold-digging and deforestation (Uryu et al, 2001).…”
Section: Total Mercury In Fish From Tele Pires Riversupporting
confidence: 42%
“…Por otra parte, Álvarez et al ( 2012), determinaron las concentraciones de MeHg en tejido muscular de seis especies del río Nechí, registrando altas concentraciones de este metal tóxico en especies carnívoras. Es conocido que la bioacumulación de metilmercurio en tejido muscular de peces por lo general obedece el siguiente orden descendiente de acuerdo al habito alimenticio: Carnivoros > detrivoros > herbívoros (Anjos et al, 2016). Sin embargo, varios estudios sugieren que la contaminación por MeHg puede estar asociada no sólo a la variabilidad de la dieta de las especies de peces y a la capacidad de migración, sino también a otras variables del medio acuático, como la dinámica de los flujos, la profundidad del agua, los niveles de mercurio en el fondo y en los sedimentos en suspensión, y en las comunidades planctónicas y bénticas (Reuther, 1994;Kasper et al, 2009).…”
Section: Discussionunclassified
“…One of the traditional examples is represented by mercury. Numerous studies investigated the presence of this metal in marine food, by sampling animal populations in the sea at particular latitudes [ 25 , 26 , 27 ]. Methylmercury bioaccumulation has severe consequences on human health, as history has taught us through the Minamata disaster (Japan, 1953).…”
Section: The Impact Of Food Contamination On the Onset Of Parkinson’s...mentioning
confidence: 99%